Analysis of the causes of neonatal death and genetic variations in congenital anomalies: a multi-center study - Yang, Xue; Bai, Ruimiao; Zhang, Juan; Yang, Yunfan; Zhang, JuanJuan; Wang, Baozhu; Li, Zhankui; Yu, Xiping (Frontiers in Pediatrics, 2024)
Background: Neonatal deaths often result from preventable conditions that can be addressed with appropriate interventions. This study aims to analyze the distribution of the causes of neonatal death and explore genetic variations that lead to congenital anomalies in Northwest China.This multi-center observational study was conducted across six medical centers in Shaanxi province, Northwest China. Clinical data were retrospectively collected from neonates admitted between 2016 and 2020. Kaplan-Meier analysis was utilized to estimate survival rates, while highthroughput sequencing platforms were employed for detecting mutations causing congenital anomalies. Results: Among 73,967 neonates requiring hospital care, 424 neonatal deaths were recorded, leading to a neonatal mortality rate of 0.57%. The primary causes of death included neonatal respiratory distress syndrome (23.8%), birth asphyxia (19.8%), neonatal septicemia (19.3%), and congenital anomalies (13.6%). The leading causes of neonatal deaths due to congenital anomalies were congenital heart defects (38.6%), bronchopulmonary dysplasia (14.0%), and inherited metabolic disorders (10.5%). Genetic analysis identified 83 pathogenic or likely pathogenic variants in 23 genes among the neonates with congenital anomalies, including four novel mutations (c. 4198+1G>T, c.1075delG, c.610-1G>A, c.7769C>T) in the ABCC8, CDKL5, PLA2G6, and NIPBL genes.Congenital anomalies represent a significant and preventable cause of neonatal deaths in Northwest China. Early detection of congenital anomalies through genetic testing and comprehensive prenatal care are crucial for reducing neonatal mortality rates and improving pregnancy outcomes.